2020
DOI: 10.1186/s12936-020-3119-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DawaPlus 3.0 and DawaPlus 4.0, deltamethrin–PBO combination nets against pyrethroid-resistant Anopheles culicifacies in experimental huts in India

Abstract: Background: The development of resistance in vectors is one of the major impediments for malaria control. Adding synergists to insecticides has proven to be an alternative choice for controlling resistant mosquitoes. DawaPlus 3.0 and DawaPlus 4.0 are new long-lasting insecticidal nets (LLINs) in which deltamethrin and a synergist, piperonyl butoxide (PBO) are added into filaments and their efficacy was tested against resistant malaria vector, Anopheles culicifacies in experimental huts in India. Methods: The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The chief reason for producing PBO-LLIN is the widespread high pyrethroid resistance levels in Anopheles mosquitoes in malaria-endemic African countries. Although the majority of previous studies found that PBO-LLIN outperformed LLIN at increasing killing power and/or reducing malaria infections [21–23,55], several studies reported reduced efficacy of PBO-LLIN against highly resistant Anopheles and Culex mosquitoes [28,30,49,5355]. We should note that it is unlikely that African Anopheles mosquitoes were exposed to PBO or PBO-synergized insecticide products before large-scale rollout of PBO-LLINs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chief reason for producing PBO-LLIN is the widespread high pyrethroid resistance levels in Anopheles mosquitoes in malaria-endemic African countries. Although the majority of previous studies found that PBO-LLIN outperformed LLIN at increasing killing power and/or reducing malaria infections [21–23,55], several studies reported reduced efficacy of PBO-LLIN against highly resistant Anopheles and Culex mosquitoes [28,30,49,5355]. We should note that it is unlikely that African Anopheles mosquitoes were exposed to PBO or PBO-synergized insecticide products before large-scale rollout of PBO-LLINs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Mozambique found that highly insecticide-resistant Anopheles funestus was also resistant to PBO-LLIN [28]. A number of other studies also found that pre-treatment of insecticide-resistant Aedes, Anopheles and Culex mosquitoes did not fully restore the mosquitoes' susceptibility to insecticides and sometimes had a very limited effect on mortality [29][30][31]. There are several possible causes for mosquito to tolerant PBO-synergized insecticides, including: A) the PBO concentration is too low or the exposure duration is too short; B) the resistance is so intense that PBO exposure cannot .…”
Section: Introductionmentioning
confidence: 99%
“…An experimental hut study conducted recently in the same area showed that the exit rate (induced exophily) of An. culicifacies in the untreated arm was 23.9% [ 19 ]. However, a higher exophily (40.5–57.5%) was recorded with the treated arms, but between them, there was no significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental hut studies conducted in West and Central Africa, Tanzania and Togo with high pyrethroid resistance showed that pyrethroid-PBO nets performed better than standard-LLINs [ 9 , 10 , 25 ], whereas in moderate to low pyrethroid resistant areas, there was little or no difference in the effect of unwashed/washed pyrethroid-PBO nets compared to unwashed/washed standard-LLINs [ 19 , 25 ]. This may be due to the wide variation in insecticide resistance levels in malaria vector species.…”
Section: Discussionmentioning
confidence: 99%